2021
DOI: 10.3390/land10101080
|View full text |Cite
|
Sign up to set email alerts
|

Land Use and Land Cover Change in the Yellow River Basin from 1980 to 2015 and Its Impact on the Ecosystem Services

Abstract: Land use and land cover change is an important driving force for changes in ecosystem services. We defined several important human-induced land cover change processes such as Ecological Restoration Project, Cropland Expansion, Land Degradation, and Urbanization by the land use / land cover transition matrix method. We studied human-induced land cover changes in the Yellow River Basin from 1980 to 2015 and evaluated its impact on ecosystem service values by the benefit transfer method and elasticity coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 72 publications
(105 reference statements)
1
12
0
Order By: Relevance
“…Ecosystem service level is gradually being restored and the ESV gradually increasing, which shows that the increased restoration of forestland, grassland and other ecological land can significantly improve the level of ecosystem services. This conclusion is in accordance with the findings of Liu et al [68]. The results also show that forestland, grassland, and other ecological land use types are the main contributors to the ESV in the YRB, mainly because the areas of forestland and grassland in the basin are large and the increase in the ESV of forestland and grassland determines the increase in the overall ESV in the YRB.…”
Section: Discussionsupporting
confidence: 92%
“…Ecosystem service level is gradually being restored and the ESV gradually increasing, which shows that the increased restoration of forestland, grassland and other ecological land can significantly improve the level of ecosystem services. This conclusion is in accordance with the findings of Liu et al [68]. The results also show that forestland, grassland, and other ecological land use types are the main contributors to the ESV in the YRB, mainly because the areas of forestland and grassland in the basin are large and the increase in the ESV of forestland and grassland determines the increase in the overall ESV in the YRB.…”
Section: Discussionsupporting
confidence: 92%
“…Land-use change has a quantifiable impact on the ESV. The implementation of the GGP effectively changed the ESV of farmland, forestland, and grassland in the region [5,40]. Table 8 shows that, as the project was implemented, the area of farmland was gradually reduced, the ESV was considerably lowered, and it shifted from 0.18% before project implementation to 7.36% after project implementation.…”
Section: Effects Of the Ggp On The Esvmentioning
confidence: 99%
“…As the largest ecological restoration project in the world, the GGP can alleviate the contradiction between the ecological environment and human activities by changing land-use types and landscape patterns and repairing ecosystem service functions and structures [30][31][32][33]. To evaluate the effects of GPP, several scholars conducted numerous tests and provided discussions on grain production [34,35], soil carbon sequestration capacity [36], ESV [37,38], land use [39,40], vegetation change [41], and other aspects. Evaluating the implementation effect of the GGP from the perspective of the ESV can provide scientific and reasonable policy suggestions for further project implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that LUCC significantly affects changes in the ESV [ 39 , 58 ]. In particular, irrational land-use change can lead to ecosystem degradation.…”
Section: Discussionmentioning
confidence: 99%